A Framework for Improving Manufacturing Overall Equipment Effectiveness - Ng, K.C.; Chong, K.E. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
The main motivation for improving productivity is to develop and implement manufacturing methods and concepts that provide stable, flexible and low cost production with high quality levels.  However in the pursuit of increasing competitiveness may lead to plant downtime; which must be minimized wherever possible.  Overall equipment effectiveness (OEE) is a metric to measure equipment performance and effectiveness and therefore, reduce equipment cost of ownership (COO). OEE topic has become progressively popular and widely used as a research discussion in operation management.  However, OEE framework for previous studies was developed on a piecemeal basis. This paper presents a new and complete conceptual framework that illustrates the most important factors that influence and contribute to OEE improvement.  The comprehensive framework is able to provide effective guidance and direction to industry practitioner on how to improve OEE.